Pengaruh Whistleblowing System Terhadap Kinerja Dengan Kesejahteraan Psikologis Dan Keterikatan Kerja Sebagai Variabel Pada Tenaga Medis RSUD Ngimbang - Nor Febrianti, Ludvia Valentina (Universitas Negeri Surabaya, 2024)
This research discusses the performance of medical personnel at Ngimbang Regional Hospital. This research analyzes the influence of the Whistleblowing system on Performance with Psychological Well-Being and Work Engagement as Mediating Variables. The object of this research is the medical staff at Ngimbang Regional Hospital, and the data collection technique uses simple random sampling techniques. The number of respondents to this study was 66 medical personnel who distributed questionnaires directly. This quantitative research uses data analysis techniques like Structural Equation Modeling on SmartPLS version 3 software. The research results show that the Whistleblowing system positively and significantly affects Performance, Psychological Well-being and Work Engagement. Psychological well-being and work engagement have a positive and significant effect on performance. Psychological well-being and work engagement have a positive and significant influence, so they act as mediating variables between the whistleblowing system and performance. This research can be a reference for the leadership of Ngimbang Regional Hospital in improving the performance of medical personnel. Organizations can expect increased productivity and overall performance by increasing psychological well-being and work engagement through an effective whistleblowing system. Employees who feel emotionally connected to their work and feel psychologically supported tend to be more enthusiastic and dedicated to making their best contribution.